Mobile Usage at the Base of the Pyramid in Kenya - World Bank (Washington, DC, 2014)
With the cost of mobile phones decreasing steadily, what was once considered a luxury good is now more commonly considered a necessity by many Kenyans, including those at the economic base of the pyramid (BoP). iHub research and research solutions Africa conducted a 6-month study in order to increase the understanding of actual usage of mobile services, products, and applications at the BoP and to understand their potential for economic and social empowerment. The study covered urban and rural areas of 6 districts in Kenya. Its findings are not nationally representative, but comparisons with representative surveys show no significant differences for key indicators, such as phone possession. The added value of the study at hand lies in the qualitative insights on choices, lifestyles, habits and mobile phone usage patterns used among phone owners at the BoP, as well as its focus on add-on services ranging from phone applications to various Internet tools. The overall objective of the study was to provide a thorough and fact-based understanding of the current and potential future demand and usage patterns of the mobile devices by the BoP in Kenya.